“Anh Nam, the attach file is my report for trip to KL”: An investigation into the emergence of a new variety of English in written Vietnamese business communication - Nguyen, Huynh Ngoc Bich (Curtin University, 2014)
This study sought to examine whether distinct, localised features of English used in business communication are emerging in the Vietnamese socio-cultural context. Both content analysis and discourse analysis were applied to texts with regard to systemic functional characteristics. The findings of the study indicate that systematic features were exhibited across the data at lexico-grammatical level as well as contextual level, together demonstrating six major features and suggesting that many issues of World Englishes be revisited.